Do the Caregivers Of Under-Fives Have Proper Health Care Seeking Behaviour for Their Children? A Study from Urban Slums of a City in Eastern India - Mohanty, Parimala; Satpathy, Sudhir Kumar; Patnaik, Sibabratta; Patnaik, Lipilekha (Journal of Nepal Paediatric Society, 2021)
Introduction: The morbidity and mortality among under-five children are many times higher in slums than more privileged urban neighbourhoods. This could be correlated with the caregivers’ behaviour too. Therefore, we intended to assess the health care seeking behaviour for their children among caregivers of under-five children in urban slums of Bhubaneswar city. Methods: It was a cross-sectional study conducted during Jan 2019 to April 2019 in Bhubaneswar, India. Data regarding health care seeking behaviour of 530 caregivers of under-five (U5) children residing in urban slums of Bhubaneswar, whose children suffered from any illness in last one month, were collected. Results: The most common childhood illnesses for which healthcare were sought were diarrhoeal diseases (30.4%) followed by respiratory infections (29.1%). A concept analysis of the predisposing factors was built up as “socio cultural context”, “economic context”, “education context”, and “individual preference” to know the health care seeking pattern. The health care seeking behaviour among the caregivers of under-five children was significantly associated with sex of child, size of the household, social group of caregiver, mother with mass media knowledge, age, education and occupation of mother, mother having BPL card, if suffering from chronic disease, decision making person for seeking health care, time lapse in approaching the health care facility and income loss due to U5 children illnesses. Conclusions: The challenge is to know about signs and symptoms of ill-health and to recognise when to seek health care services. Measures can be taken to promote awareness for seeking timely appropriate care. There is a need to develop locally adapted behaviour change communication interventions for childhood Illnesses.